2010
DOI: 10.1007/s11274-010-0584-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress induced cross-protection against environmental challenges on prokaryotic and eukaryotic microbes

Abstract: Prokaryotic and eukaryotic microbes thrive successfully in stressful environments such as high osmolarity, acidic or alkali, solar heat and u.v. radiation, nutrient starvation, oxidative stress, and several others. To live under these continuous stress conditions, these microbes must have mechanisms to protect their proteins, membranes, and nucleic acids, as well as other mechanisms that repair nucleic acids. The stress responses in bacteria are controlled by master regulators, which include alternative sigma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 185 publications
1
40
0
9
Order By: Relevance
“…It is plausible that, in the present study, iron starvation and microaerobic conditions exerted a compound influence on H. hydrothermalis tolerance of differences in temperature and salinities either directly or as a consequence of secondary stress responses (such as those induced by a reduction in pH under CO 2 -enriched conditions; see Table S1 in the supplemental material). Indeed, exposure to a given extreme can frequently confer cross-protection against other environmental stressors in both prokaryotes and eukaryotes, due to overlapping physiological adaptations and stress-response networks (8,60,(62)(63)(64)(65).…”
Section: Resultsmentioning
confidence: 99%
“…It is plausible that, in the present study, iron starvation and microaerobic conditions exerted a compound influence on H. hydrothermalis tolerance of differences in temperature and salinities either directly or as a consequence of secondary stress responses (such as those induced by a reduction in pH under CO 2 -enriched conditions; see Table S1 in the supplemental material). Indeed, exposure to a given extreme can frequently confer cross-protection against other environmental stressors in both prokaryotes and eukaryotes, due to overlapping physiological adaptations and stress-response networks (8,60,(62)(63)(64)(65).…”
Section: Resultsmentioning
confidence: 99%
“…These differences may be due to thermometer accuracy, because even few decimals in degrees Celsius would change the conidial viability (Rangel et al, 2005b). Another possibility to explain these differences is due to culture medium which often changes the tolerance to stress; less nutritive or nutrient poor medium affords higher tolerance to UV-B radiation and heat (Rangel, 2011;Rangel et al, 2006aRangel et al, , 2008Rangel et al, , 2004Rangel et al, , 2011. We did not use yeast extract to supplement the potato dextrose agar medium, which was used before (Rangel et al, 2005b(Rangel et al, , 2006b.…”
Section: Resultsmentioning
confidence: 99%
“…The stress responses in bacteria are controlled by master regulators, which include alternative sigma factors such as RpoS (22). van Hoek et al (23) reported that a fully functional RpoS system is an advantage for the long-term survival of Escherichia coli O157 in the manure-amended soil environment.…”
Section: Discussionmentioning
confidence: 99%